A brief neurocognitive assessment of patients with psychosis following traumatic brain injury (PFTBI): Use of the Repeatable battery for the Assessment of Neuropsychological Status (RBANS). (30th March 2016) - Batty, Rachel A.; Francis, Andrew; Thomas, Neil; Hopwood, Malcolm; Ponsford, Jennie; Rossell, Susan L.
Abstract: Patients who develop psychosis following a traumatic brain injury (PFTBI) show impaired neurocognition; however, the degree of impairment has not been empirically investigated using a standardised battery. We administered the Repeatable Battery for the Assessment of Neuropsychological Status (RBANS) to patients with PFTBI ( n =10), and to three groups of controls: traumatic brain injury (TBI) ( n =10), schizophrenia ( n =23), and nonclinical controls ( n =23). The results confirmed that the cognitive neuropsychological profile of dually-diagnosed patients with PFTBI is significantly and substantially impaired. Seventy per cent of patients with PFTBI received a neuropsychological classification between the "extremely low" and "low average" ranges. Group-wise analyses on the RBANS indices indicated that patients with PFTBI had the lowest (Immediate Memory, Attention, Delayed Memory, Total Score), or equal lowest (visuospatial, equivalent with schizophrenia patients) scores, with the exception of the Language Index where no group differences were shown (however, the mean PFTBI score on the Language Index was two standard deviations below the RBANS normative score). These findings provide novel evidence of impaired cognitive neuropsychological processing in patients with PFTBI using a standardised and replicable battery. Highlights: The PFTBI cognitive neuropsychological profile is significantly and substantially impaired. PFTBI deficits exceed those demonstrated in TBI and schizophrenia alone. The RBANS is an effective method of neuropsychological assessment in PFTBI. This is the first standardised neuropsychological assessment of a cohort of PFTBI patients.